Assessment of esophagectomy videos on YouTube: Is peer review necessary for quality? - (:unkn) unknown (My University, 2022)
Introduction: Various online platforms, such as YouTube, are used for surgical education. Esophageal surgery is sophisticated and surgical videos may help reduce the time it takes for surgeons to learn these complicated operations. There is no clear consensus regarding the quality and reliability of esophagectomy videos on YouTube. We aimed to evaluate esophageal surgery videos published on YouTube in terms of quality and reliability.Methods: The keywords \"esophagectomy\" and \"surgery\" were both searched on YouTube and the first 150 results were evaluated. Eighty two videos were included in the analysis. The quality and reliability of the videos were determined using the esophagectomy scoring system (ESS) developed by the authors, the Journal of the American Medical Association benchmark criteria, and the video power index.Results: A total of 82 videos were reviewed. About two-thirds of the videos demonstrated the Ivor Lewis technique and included surgeries performed using the thoracoscopic/laparoscopic method. The videos were analyzed as per the source of the upload: academic (25.7%), industry -sponsored (9.7%), or individual (64.6%). When the scores were compared by the origin of the videos, industry-sponsored videos scored significantly higher than the videos produced by individuals and academic centers (P = 0.01). While the ESS and Journal of the American Medical Association benchmark criteria scores were significantly correlated (P = 0.00), no correlation was found between video length, video power index score, and ESS score. Conclusions: Conducting a professional evaluation of videos before they are published on YouTube may enhance video quality. Moreover, valuable videos of better quality can be produced by improving the ESS and by assessing more videos.(c) 2022 Elsevier Inc. All rights reserved.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Health Sciences; CERRAHİ; Klinik Tıp; Klinik Tıp (MED); SURGERY; CLINICAL MEDICINE; Clinical Medicine (MED); Cerrahi; Surgery; Educational technology; Esophagectomy; Thoracic surgery; Video -assisted surgery; YouTube; INFORMATION; COVID-19